1996
DOI: 10.1088/0953-2048/9/10/012
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase sintering and microstructure development of Ag-clad Tl-1223 superconductor

Abstract: The phase evolution and electrical properties of Tl-1223 tapes were explored near the incongruent melt temperature. Liquid phase evolution was monitored as a function of time and temperature by an acoustic velocity monitor. The phase development kinetics for Tl-based superconductors are more than one order of magnitude faster than the kinetics of Bi-based superconductors. Three separate powder mixtures (Tl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Due to this, on the one hand, Ca and Cu can easily react with Ba and Tl, and on the other hand, a liquid phase is very likely to form at synthesis temperatures. Cheung and Ruckenststein [33,34] observed glassy phases at 850-865 • C. Hagen et al [35] monitored liquid phase evolution in 1223 PIT-tapes as a function of temperature and oxygen partial pressure, by the in situ acoustic velocity method. They found that the melting temperature is between 810 • C and 875 • C when oxygen environment changes between 1% O 2 and 100% O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, on the one hand, Ca and Cu can easily react with Ba and Tl, and on the other hand, a liquid phase is very likely to form at synthesis temperatures. Cheung and Ruckenststein [33,34] observed glassy phases at 850-865 • C. Hagen et al [35] monitored liquid phase evolution in 1223 PIT-tapes as a function of temperature and oxygen partial pressure, by the in situ acoustic velocity method. They found that the melting temperature is between 810 • C and 875 • C when oxygen environment changes between 1% O 2 and 100% O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1234 phase. On the other hand, when oxygen pressure decreases the Tl-vapour pressure increases [9] and according to the same phase diagram [3] the equilibrium should shift in the opposite direction, i.e. to a 1223 phase formation.…”
Section: Tl and Oxygen Content In The Starting Composition Of The Sam...mentioning
confidence: 99%
“…From the different behaviour regarding J c in the two samples synthesized with the same heating rate (0.11 • C min −1 ), it seems that the final heat treatment temperature is important in order to enhance the critical current density. For a given oxygen partial pressure Hagen et al [9] showed that there is an optimum temperature for the synthesis of Tl-1223 tapes with maximum J c . However, the difference between the values of J c in our samples was relatively low.…”
Section: Heating Ratementioning
confidence: 99%
“…Various phases of Tl-based superconductor can be prepared for both series. For high-current applications in strong magnetic fields, the single layer phase seems to have better advantage than the double layer phase [1,13,14]. In the single layer phases, the stronger coupling between conducting Cu-O planes separated by single-layer insulating Tl-O is responsible for the better J c property in higher magnetic fields [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the single layer phases, the stronger coupling between conducting Cu-O planes separated by single-layer insulating Tl-O is responsible for the better J c property in higher magnetic fields [7,15]. Thus, single layer Tl-based phases such as the Tl-1223 and Tl-1212 are the better choice due to their reasonably high T c with excellent J c in the presence of magnetic fields [14][15][16][17][18][19]. The Tl-1212 phase is expected to preserve a higher fraction of its zero field J c values at higher fields due to stronger pinning between the Cu-O plane [20].…”
Section: Introductionmentioning
confidence: 99%